Get Normal : How partnering whith God transforms your life - Maxon, Ben (Departa mento Ministerio de Myordomía de la Conferencia General de la Iglesia Adventista del Séptimo Día, 2010)
As you read and journey with us on this spiritual experience of knowing God personally and allowing Jesus to be Lord of every facet of your life, our prayer is that you will find joy and peace in your heart that will transform you from inside out. Contents: Chapter 1 REALITES Chapter 2 DISCIPLES Chapter 3 STORY Chapter 4 GOD Chapter 5 STEWARSHIP Chapter 6 LORDSHIP Chapter 7 LOYALTIES Chapter 8 TITHING Chapter 9 ATTITUDE Chapter 10 PARTNERS Chapter 11 TRANSFORMATION Chapter 12 PRESENCE Chapter 13 PRIORITIES